2017
DOI: 10.26735/16586794.2017.018
|View full text |Cite
|
Sign up to set email alerts
|

Age, Sex and Stature Estimation from Footprint Dimensions

Abstract: two were breadth dimensions from both left and right footprints: breadth at ball (BBAL), breadth at heel (BHEL). In addition, 2 indexes were recorded: heelball Index (HBI) and footprint index (FPI). All data were analyzed statistically using Student's t-test, regression coefficient and Pearson's correlation for the estimation of sex on the basis of footprint dimensions.The T1 in left footprints was greater than right footprints in males, while T1 and BBAL were both found to be greater in left footprints than r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
2
5
1
Order By: Relevance
“…Foot Index in women relating to the left foot was higher, namely R: 38.8 and L: 38.9, and the FI of elderly women without any significant differences (p = 0.717). Our acquired Foot Index values are higher compared to the results of Singh and Yadav (2017), who found in their study the rightward FI of 36.9 ± 3.5 and the leftward FI of 36.1 ± 4.9; the left foot FI values were higher, however, the differences were not significant (p = 0.056). Results in Moudgil et al (2008) study were reversed; women had higher right foot FI.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Foot Index in women relating to the left foot was higher, namely R: 38.8 and L: 38.9, and the FI of elderly women without any significant differences (p = 0.717). Our acquired Foot Index values are higher compared to the results of Singh and Yadav (2017), who found in their study the rightward FI of 36.9 ± 3.5 and the leftward FI of 36.1 ± 4.9; the left foot FI values were higher, however, the differences were not significant (p = 0.056). Results in Moudgil et al (2008) study were reversed; women had higher right foot FI.…”
Section: Discussioncontrasting
confidence: 89%
“…Ewunonu, Egwu, Eteudo and Ajoku (2014) study demonstrated occurrence of bilateral asymmetry in the foot dimensions in young adults; women in this study had their right foot longer and wider than the left one. Singh and Yadav (2017) found side differences only in the foot length parameters measured from the most proximal point of the heel (pternion) to the most distal point of the big toe. They also found significant differences in the width of the foot.…”
Section: Discussionmentioning
confidence: 78%
“…Dismembered hands or hand impressions are a common type of physical evidence recovered and/or easily obtained in disaster victim identifications and crime scene investigations. Several research investigations have been carried out to determine the sex of an individual by taking the measurements of hand dimensions (for example HL and HB) (Aboul-Hagag et al 2011;Sen et al 2011;Uhrova et al 2015;Ibrahim et al 2016;Caplova et al 2017;Singh and Yadav 2017;Arifi et al 2018;Rongpi and Mondal 2019), foot dimensions (foot length and foot breadth) (Singh and Bhasin 1989;Singh and Phookan 1993;Kanchan and Rastogi 2009;Pal et al 2016;Singh and Yadav 2017;Zulkifly et al 2018;Adelakun et al 2019;Singh et al 2019b), fingers (index or ring finger) and phalanges (Robling and Ubelaker 1997;Kanchan et al 2013;Barrett and Case 2014;Bakholdina et al 2016;Gupta et al 2017;Singh et al 2019b). There is almost a complete absence of such forensic investigation among the ethnic and indigenous population of northeast India.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of stature or sex from various linear measurements, such as hand and foot dimensions, is the easiest components for personal identification in forensic science and medico-legal aspects (Kanchan et al 2010a,b;Sen et al 2011;Dey and Kapoor 2015;Jee et al a,b 2015;Sen et al 2015;Kim et al 2018;Asadujjaman et al 2019;Singh et al 2019a). It is common to find fragmented body parts, such as hand and foot in disaster, crime scene, explosions, airplane and train accidents (Kanchan et al 2010a,b;Jee et al 2015;Bindurani et al 2017;Singh and Yadav 2017;Kim et al 2018;Zulkifly et al 2018;Asadujjaman et al 2019;Rongpi and Mondal 2019;Singh et al 2019b). In such cases, estimation of the sex as well as stature from the fragmented body parts bears an utmost importance in the field of forensic science and medico-legal aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation